(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
It’s considered obligation to show the realistic and appropriate position of the media today, through their characteristics, strength, power, all the way to the distinctive range of relationships in which they find themselves. The key question as a guide in this sense is - what the media really are, and what is their connection with the authorities (politics), how strong is the link between the media and the authorities, and in the end what are the advantages/benefits, and what harms this bond between them produces for both sides. Then it’s important to analyze the connection between these occurrences, which are undeniably intertwined with the media and the authorities, and their employees (on both sides), and what can be consistently supported by a couple of examples, which are today a handful of global diversity, as well as within local and regional centers. It’s also important to touch on the inevitable topic of the market, the role of the media in the market and the opportunities it provides to both – the media and those who uses it. Important is the industrial culture as a reflection of media content, thanks to which today we have a lot of offers, demand and choices (something like a buffet – something for everyone), which has developed under the influence of the media and is successfully developing every day, reform and expand. It’s necessary to reiterate the indisputable facts that unequivocally indicate that the media, in their absolute power, are trying to be used to their full capacity. But with certainty, it can be said, there are few who notice how much it affects each person individually in a negative connotative sense, but also human communities around the world, by changing, distorting, transforming, blurring social values. On the other hand, due to their extremely great power and potential, the media are desirable to almost everyone, and certainly most to the political elites.